Factors that Contributed the Management of Stage 1 Labor Pain Maternity Mothers the Delivery Room Dr. Derajat Prawiranegara Hospital Serang in 2019 - Umar, Ernawati (KnE Life Sciences, 2021)
In women who give birth normally, about 90% of mothers feel labor pain Stage 1. Medically, the pain is categorized as sharp and hot or somatic-sharp and burning. The pain typically starts when the head appears in the vagina. The tissue between the vagina and the anus (perineum) is stretched tight due to the head pushing it open. The mother feels pain due to the tearing of the tissue. Labor pain causes anxiety and fear so that the need for oxygen increases, blood pressure increases, muscles become tense, this condition will lead to prolonged labor, and can be a contributing cause in the death of mothers and babies. To determine the factors that contribute to pain during the first stage of labor in the delivery room dr. Derajat Prawiranegara Hospital Serang in 2019. The research design used was descriptive observational research, to see the factors that contribute to the management of Stage 1 labor pain. The statistical analysis indicates a significant relationship between education, family support, and coping mechanisms with the management of period 1 intrapartum pain, with p-value < 0,05%, while the factors that were not related were age, and parity, for the Stage 1 of labor pain, because the P-value > 0.05%.